The incidence of administrative cases against dentists in the Philippines from 1980-1998 - De Leon, Joseph Lemuel E.
Little is known about the incidence of administrative cases against Philippine Dentists. This research consists mainly of descriptive study of the ratio of administrative cases filed against dental practitioners in the Professional Regulation Commission (PRC) to the number of registered Philippine Dental Association (PDA) dentists, with the following specific objectives: to compute for the average number of administrative cases filed from 1980-1998, to determine what administrative offense is most often committed, to determine the type of decisions given to these administrative cases. This was done by collecting the administrative at the PRC from 1980-1998 and the number of registered PDA dentists from 1993-2000. The study concludes that each year 1 out of 2.763 dentists is filed with an administrative case. There is an average of 5 cases every year, 67.2% of which was dismissed while 19.3% remains pending and 15.6% were found guilty. Immorality and Dishonorable Conduct are the most prevalent charges.